Profile of Teaching Skills for PAUD Teachers at Immanuel Kids Kindergarten Medan Amplas - Arbinauli Purba; Srinahyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to describe the teacher's teaching skills, namely the skills of opening and closing lessons, skills of asking questions and skills of giving reinforcement in class. The method used in this research is descriptive qualitative. This research was conducted from March 21 to May 25 2023. The data sources for this research were class teachers at Immanuel Kids Kindergarten Medan Amplas as many as 3 teachers. Data collection techniques with observation techniques and unstructured interviews. Data were analyzed using Milles and Humberman data analysis. Testing the validity of the data is done by triangulation. The results of the study show that: 1) the skills of opening and closing lessons carried out by the three teachers in the class have emerged. This can be seen from, the teacher has implemented several aspects of the skills of opening and closing lessons but not completely, 2) the questioning skills carried out by the three teachers as well has emerged, this can be seen when the teacher can express questions clearly, give children time to think and make demands on children to find the correct answer, 3) the skills of giving reinforcement to the three teachers in the class have also appeared, this can be seen when the teacher has implemented all aspects reinforcement skills.